Development Of An E-Module Based On A Mind MAP Strengthening Student's Critical Thinking In Class IV SD - Khuri, Atiu Dawil; Kusumaningrum, Shirly Rizki; Dewi, Radeni Sukma Indra (Jurnal Ilmiah Mandala Education (JIME), 2022)
21st-century learning requires high-level thinking skills including the 4Cs (critical thinking, communication, collaboration, and creativity) which can be pursued through developing e-modules. This research is research and development (Research and Development). The aim of the research is to develop an e-module on the Mindmap-based Part of Plants. The development process was adapted from the Plomp e-model development which consists of 5 phases, namely; the initial investigation phase; the design phase; the realization/construction phase; the evaluation, and revision test phase; and the implementation phase. This research was carried out in the odd semester of the 2022/2023 Academic Year with the research subjects being grade 4 students at UPT SD Negeri Bajang 02. The results of this study indicate that the e-module on plants based on mind mapping is declared valid with an average rating of 3,